Adsorption characteristics of cesium onto calcium-silicate-hydrate in concrete powder and block. (November 2020) - Kang, Seunghee; Lee, Jeshin; Park, Sang-Min; Alessi, Daniel S.; Baek, Kitae
Abstract: The concrete building and paved roads in the urban areas can be exposed to cesium (Cs + ) in case of the accidental release to environment. The adsorption kinetics of Cs + onto concrete powder was well-represented by the pseudo-second-order kinetic model and intra-particle diffusion model. Both Langmuir and Freundlich isotherm models adequately described the adsorption of Cs + onto the concrete powder. Lower temperature favored the adsorption of Cs +, and the activation energy was estimated as 1.57 kJ/mol, which indicates a physical adsorption process. Additionally, the adsorption of Cs + onto the concrete powder was spontaneous ( Δ G < 0 ), exothermic ( Δ H < 0 ), and its adsorption formed a stable arrangement onto the concrete powder ( Δ S < 0 ). The adsorption of Cs + onto the concrete block was similar to that onto the powder, where the activation energy was 25.64 kJ/mol indicating physical adsorption. The presence of Na + enhanced the adsorption of Cs + because Na + lowered the competitive inhibition of K + on the adsorption of Cs + based on hydrated radius and hydration enthalpy. The amounts of Cs + adsorbed onto C–S–H gel were not substantial and the adsorption was slow, but it should be considered in an urban area due to a huge coverage of concrete. Graphical abstract: Image 1 Highlights: Few amounts of Cs + adsorbed physically onto C–S–H gel in concrete. Adsorption of Cs + onto C–S–H gel was spontaneous and exothermic. Adsorption of Cs + onto C–S–H gel was slow. Co-presence of Na + and K + enhanced adsorption of Cs + . Adsorption of Cs + onto concrete is not too serious.